Rubber Plantations in Sri Lanka: An Examination of Historical and Current Grievances in the Pahala Karannagoda Grama Niladari Division - Lakmini Gamage; K.A. Udani Udya (The Open University of Sri Lanka, 2023)
Plantation agriculture was introduced to Sri Lanka by the Dutch, but it was under British rule that several crops were cultivated on a large scale, including coffee, cinchona, cocoa, tea, and rubber. Among these crops, rubber was first cultivated in the Kalutara district and later spread to other parts of the country, becoming one of Sri Lanka's major export crops during the British period. This paper explores the history of rubber plantations in Sri Lanka and investigates the grievances of rubber planters in the Pahala Karannagoda Grama Niladari division of the Kalutara district. The study aims to examine the History of rubber cultivation during the British period in Sri Lanka and the challenges faced by rubber planters in the selected area in the present day. A mixed-method approach is used for this research. Data was collected using field investigations and observing text documents. Field investigations were conducted in the Pahala Karannagoda Grama Niladari division. Key informant interviews were conducted with 73 purposive samples. Data was analyzed based on the thematic analysis method employing rural grievances theoretical principles. The findings of the study suggest that rubber plantations gradually developed and contributed significantly to the country's economy, and rubber planters in the Pahala Karannagoda Grama Niladari division face various challenges related to climate change, labor issues, and lack of government support. The paper concludes with recommendations for addressing these issues and improving the conditions of rubber planters in the region.